Designing A Research Study on ECU’s Recycling Habits Through Prototyping, Pivoting, and Failing - High, Mattie; Agostini, Marco; Banzon, Caroline; Rubino, Emily; Shingleton, Will (East Carolina University, 2021)
According to the National Waste and Recycling Association, approximately 25% of items in recycling bins are considered nonrecyclable contamination, obstructing recycling efforts nationwide. On ECU’s campus, contamination in outdoor recycling has negatively impacted the overall recycling efficiency. The current design and color of bins may be a factor. We are testing whether a change in color has an impact on the rates of recycling and the percent of contamination. To test this, we will conduct an experiment with different colored bins that are more closely associated with recycling, like blue and green. The current purple bins will be used as a control. The ECU bus stop close to Greene Residence Hall and the Eakin Student Recreation Center was selected as the testing site. Each week, the bin will be audited for contamination and rotated weekly to the next test color. At the conclusion of the experiment, we hoped to find a bin that promoted the cleanest outdoor recycling stream possible. With the data collected before the onset of the COVID-19 pandemic, we hope to present our findings to administration to advocate for change and provide insight on recycling during COVID-19.
Keywords: recycling; sustainability; COVID-19; pivoting; HNRS